TELAAH LINGUISTIK INTERDISIPLINER DALAM MAKROLINGUISTIK - Muhassin, Mohamad (Universitas Islam Negeri Raden Intan Lampung, 2014)
This article focuses on the study of interdisciplinary linguistics in macrolinguistics. Linguistics is a scientific study of language. In its development, linguistics covers two major areas, i.e. microlinguistics and macrolinguistics. Microlinguistics discusses the internal structures of language such as phonology, morphology and syntax. Moreover macrolinguistics studies the relation between language and the world outside language. It comprises two sub-disciplines i.e. interdisciplinary and applied linguistics. Interdisciplinary linguistics is a joint-study of linguistics and other sciences. Some studies included in interdisciplinary linguistics are phonetics, stylistics, language philosophy, sociolinguistics, semiotics, forensic linguistics, anthropolinguistics, epigraph, psycholinguistics, ethnolinguistics, philology, genolinguistics, and ecolinguistics.